Nutrition Risk Screening and Related Factors Analysis of Non-hospitalized Cancer Survivors: A Nationwide Online Survey in China - Wang, Fang; Dong, Qi; Yu, Kang; Li, Rong-rong; Fu, Ji; Guo, Jia-yu; Li, Chun-wei (Frontiers in Nutrition, 2022)
Purposes: This study investigated the nutritional problems and risks of Chinese non-hospitalized cancer survivors through an online survey. Methods: The survey included nutritional and clinical questions distributed to non-hospitalized cancer survivors. All data were screened and analyzed with strict quality control. Nutrition Risk Screening-2002 (NRS-2002) was adopted and the related factors were analyzed. Results: 6,685 questionnaires were included. The prevalence of nutritional risk was 33.9%, which varied according to age, sex, cancer type, TNM staging, oncologic treatment, etc. Patients with leukemia and digestive cancer had the highest NRS-2002 score (3.33 ± 1.45 and 3.25 ± 1.61); the prevalence of nutritional risk (NRS-2002 ≥ 3) was 66.7% and 55.1%, respectively. Patients with a higher TNM stage had higher NRS-2002 scores in non-digestive cancer, which was not seen in digestive cancer. Among digestive, bone, nervous, and respiratory cancer patients, the NRS-2002 score mainly consisted of “impaired nutritional status,” which coincided with the “disease severity score” in leukemia patients. Nutrition intervention was achieved in 79.7% and 15.2% of patients with nutritional risk and no risk. Of the patients, 60.3% exhibited confusion about nutritional problems, but only 25.1% had professional counseling. Conclusions: Nutritional risk screening and assessment are needed to cover non-hospitalized cancer survivors to provide nutrition intervention for better clinical outcomes and quality of life. By an online survey, the nutritional risk of non-hospitalized cancer survivors was found high in China, but the nutrition support was not desirable. The composition of nutritional risk should also be aware.